Initial vocational training from a company perspective : a comparison of British and German in-house training cultures - Pilz, Matthias [Verfasser] (My University, 2009)
"Vocational training and skills are playing an increasingly important role in the developed economies. However, both the vocational education structure and the underlying philosophy and culture of education and training vary from country to country. What is clear, though, is that employers play a crucial role in all cases; this paper explores the reasons why companies in different countries are willing to invest in initial vocational education and how they do so. The paper will focus on Great Britain and Germany as examples of a market-led model and a state-directed model, respectively. Interviews with employers in both countries show that, in Britain, initial vocational education is strongly task-related in most cases or else is seen as the employee's private, individual concern. In Germany, by contrast, a much broader range of initial vocational education is available and is viewed as an integral part of company culture." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.2 Unternehmen und Behörden; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Betriebliche Berufsausbildung; Betrieb; Ausbildungsbereitschaft; Ausbildungsinvestition; Unternehmenskultur; Internationaler Vergleich; Bundesrepublik Deutschland; England